Bilateral optic nevritis in a sickle cell anaemia carrier? – a rare clinical presentation - Rodrigues, Paulo (2004)
Sickle cell anaemia is one of the oldest known haemoglobinopathies, occurs frequently and is spread worldwide. The syndrome is highly polymorphic with clinical features ranging from mild symptoms to severe presentations. Severe forms of the diseases are only frequent in the homozygotic form (SS) and double heterozygotes, while sickle cell carriers are generally assymptomatic. Ocular manifestations are frequent in sickle cell anaemia and SC disease, occurring very rarely in heterozygotes, as stated. The authors describe a severe clinical case of sickle cell trait in a young female patient, with exceptional ocular manifestations (bilateral optic nevritis).